Educational mobility of Second-Generation Turks Cross-national perspectives - Schnell, Philipp (Amsterdam University Press, 2014)
This definitive study investigates the variations in educational mobility of Turkish second-generation immigrants in France, Austria and Sweden. The findings show that differences are most pronounced in the Austrian education system, can be seen clearly in France and are least pronounced in Sweden. Schnell underscores the importance of both individual characteristics and institutional ones, but the institutional arrangements of education systems are found to matter more for the outcome of this mobility process.